Detecting O-GlcNAc using in vitro sulfation - Wu, Zhengliang L (Oxford University Press, 2014)
O-linked β-N-acetylglucosamine (O-GlcNAc) glycosylation, the covalent attachment of N-acetylglucosamine to serine and threonine residues of proteins, is a post-translational modification that shares many features with protein phosphorylation. O-GlcNAc is essential for cell survival and plays important role in many biological processes (e.g. transcription, translation, cell division) and human diseases (e.g. diabetes, Alzheimer's disease, cancer). However, detection of O-GlcNAc is challenging. Here, a method for O-GlcNAc detection using in vitro sulfation with two N-acetylglucosamine (GlcNAc)-specific sulfotransferases, carbohydrate sulfotransferase 2 and carbohydrate sulfotransferase 4, and the radioisotope (35)S is described. Sulfation on free GlcNAc is first demonstrated, and then on O-GlcNAc residues of peptides as well as nuclear and cytoplasmic proteins. It is also demonstrated that the sulfation on O-GlcNAc is sensitive to OGT and O-β-N-acetylglucosaminidase treatment. The labeled samples are separated on sodium dodecyl sulfate–polyacrylamide gel electrophoresis and visualized by autoradiography. Overall, the method is sensitive, specific and convenient.